Bioremediation of Spent Bleaching Earth (SBE) Wastes using Lipolitic Bacteria (Bacillus cereus) with Variation of Inoculum Volume - Maria Lusia; Nuni Gofar; Hary Widjajanti (Science and Technology Indonesia, 2018)
Spent bleaching earth (SBE) is a solid waste was generated from the CPO refining step into cooking oil. SBE that was discharged directly into the environment has the potential to pollute the environment, because in the SBE waste contained oil and acid residues, which are easily to be oxidized and flammable. Therefore, SBE must be processed first before being discharged into the environment. One way to manage SBE is by bioremediation. Bioremediation is a method on cleaning the environment from contaminants by using biological agents, such as bacteria, fungi etc. The bacterial isolates used in this study were Bacillus cereus. This study aims to obtain the best inoculum and to know the ability of Bacillus cereus bacteria in degrading the oil content in SBE waste. This study used Completely Randomized Design with the volume of Bacillus cereus bacteria inoculum as a treatment, consisting of 6 treatment levels of 0 mL kg-1, 25 mL kg-1, 50 mL kg-1, 75 mL kg-1, 100 mL kg-1, 125 mL kg-1. Each treatment level was repeated 3 times, so taht 18 experimental units were obtained. Observation was done once a week, in a month. Parameters observed were bacterial population, percentage of oil degradation, and oil content degradation. The best treatment result for the bacterial population was obtained at the treatment of 100 mL kg-1, at week 4 which was 7,4 x 108 cfu g-1, and for the oil degradation was obtained at 50 mL kg-1 on the treatment at week 4 as big as 90,43%.